Outcomes of integrated surgical wound treatment mode based on tibial transverse transport for diabetic foot wound - Chang, Shusen; Zhang, Fang; Chen, Wei; Zhou, Jian; Nie, Kaiyu; Deng, Chengliang; Wei, Zairong (Frontiers in Surgery, 2023)
Background: Diabetic foot ulcer (DFU) is frequently difficult to heal and finally leads to amputation, resulting in high mortality rate in diabetic patients. To date, effective and optimal therapies are still lacking. This study aims to investigate the efficacy of integrated surgical wound treatment (ISWT) mode on diabetic foot wound. Methods: From January 2021 to December 2021, 13 diabetic foot patients with Wagner grade 3 to 4 were treated with ISWT mode, which combined TTT technique with debridement, induced membrane technique, vacuum sealing drainage (VSD) technique and skin grafting technique. The time of wound healing, the skin temperature at midpoint of dorsum of affected foot (T), visual analogue scale (VAS) score and ankle-brachial index (ABI) was measured before and after surgery. CTA examination of the lower extremity arteries was performed at the end of the cortex transport to evaluate the small arteriolar formation of the lower extremity. The complications occurred in each patient were recorded. Results: 13 patients with age ranging from 45 to 66 years were followed up for 3 to 13 months. All patients healed completely without amputation being performed, no serious complications were found except for one case of nail channel infection. The mean healing time was 25.8 ± 7.8 days, with a range of 17 to 39 days. The mean time of carrying external fixation scaffolds and resuming walking was 71.8 ± 10.0 and 30.8 ± 9.1 days, with a range of 56 to 91 days and 18 to 45 days, respectively. The skin temperature at midpoint of dorsum of affected foot (T), VAS and ABI was all improved significantly at 3 months after surgery. Furthermore, CTA examination showed an increase in the number of lower extremity arteries and a thickening in the size of small arteriolar compared with those of pre-operative, and the collateral circulation of lower extremity was established and interweaved into a network. Conclusion: Integrated surgical treatment of diabetic foot wound can achieve more satisfactory clinical results.